The Value of 16-cm Wide-Detector Computed Tomography in Coronary Computed Tomography Angiography for Patients With High Heart Rate Variability. Issue 6 (November 2018) - Chen, Yuhuan; Wei, Donghong; Li, Dou; Liu, Zhentang; Hu, Zhijun; Li, Michelle; Jia, Yongjun; Yu, Yong; Han, Dong; Ren, Ranzhi; Yu, Nan; He, Taiping
Abstract : Objective: The aim of this study was to investigate radiation dose and image quality of coronary computed tomography (CT) angiography (CCTA) for patients with high heart rate variability (HRv) using 16-cm wide-detector CT scanner. Methods: One hundred sixty-six patients with uncontrolled heart rate underwent CCTA on a 16-cm wide-detector CT system and were divided into 2 groups based on their HRv for analysis: group A (n = 95, HRv ⩽10 beats/min [bpm]) and group B (n = 71, HRv >10 bpm). Images in both groups were reconstructed with motion correction algorithm. Subjective and objective image qualities were analyzed. Results: There were no significant differences in age, body mass index, and heart rate (68.1 ± 11.4 vs 67.6 ± 12.3 bpm) between the 2 groups ( P > 0.05). However, group B had significantly higher HRv than group A (33.5 ± 24.4 vs 7.8 ± 1.2 bpm, P < 0.001). All images were acceptable for clinical diagnosis. Compared with group A, image quality scores in group B decreased slightly (4.1 ± 0.5 vs 4.0 ± 0.6). However, the difference was not statistically significant. The mean effective doses were both relatively low at 2.2 ± 1.1 mSv in group A and 2.6 ± 1.4 mSv in group B. Conclusions: Single-heartbeat free-breathing CCTA can be performed for patients with high HRv using 16-cm wide-detector CT scanner to achieve diagnostic image quality with low radiation dose.